The Study on Impacts of Financial Crowdsourcing of Iranian Football Clubs: A Content Analysis Approach - Mohamad Najmi; Abbas Naghizadeh Baghi; Nasrin Azizian Kohan; Mehrdad Moharramzadeh (Sports Business Journal)
Purpose: As an innovative approach to financing projects and research, crowdfunding allows interested individuals and members of the scientific community to directly support research projects and help promote and develop scientific activities. The current study was conducted to identify the consequences of financial crowdsourcing on Iranian football clubs using a content analysis approach.Methodology: This research is applied in terms of purpose and qualitative in terms of data collection method and was conducted with a content analysis approach. The statistical population of this research includes presidents and vice presidents of the football federation, the country's football league, presidents of football boards, managing directors, and board members of football clubs in the provinces, selected using purposeful and snowball sampling, continuing until theoretical saturation was reached. Moreover, 15 interviews were conducted. Research data analysis was performed using MAXQDA2020 software. In this research, to check the validity of the methods of validity, transferability, reliability, and verifiability and to calculate reliability, the process of agreement between coders and determination of Fleiss' kappa coefficient was used.Findings: The benefits of financial crowdsourcing include 90 sub-themes grouped into three main themes: organizational, social, and individual consequences.Originality: In general, crowdfunding, as an innovative and practical approach, can significantly increase financial resources for football clubs. It can also provide a space for creating economic innovations in sports and football. This research emphasizes the importance and value of collective investment in promoting the sports and financial sector of society and its role in fostering development and progress in this field.